The entrepreneurial support and the performance of new venture creation: the mediation effect of the acquisition of skills and the learning of novice entrepreneurs - Fitouri Mohamed; Samia Karoui Zouaoui; Akram Bel Haj Mohamed (Cogent Social Sciences)
This research endeavors to explore the impact of entrepreneurial coaching on the performance of start-ups. Employing a quantitative research methodology, data were gathered through a questionnaire-based survey. Analysis of the data was conducted using SmartPLS (Partial Least Squares) software, allowing for the assessment of discriminant validity and testing our conceptual model. The outcomes of this investigation present compelling evidence supporting the notion that entrepreneurial coaching significantly influences the performance of recently established businesses. Findings from this study contribute significantly to enhancing our comprehension of the intricate relationship between coaching, entrepreneurial support, and the outcomes of new business creation. The results reveal a substantive connection between the provision of entrepreneurial support and the positive performance outcomes of newly formed enterprises. These findings carry practical implications for various stakeholders invested in fostering the growth of start-ups. Entrepreneurs can gain valuable insights into the positive impact of receiving coaching, encouraging them to seek and leverage such support. Support organizations can use these findings to refine their strategies and tailor their coaching programs to optimize outcomes for new businesses. Policymakers can benefit from understanding the tangible benefits of entrepreneurial coaching, informing the development of policies that foster a conducive environment for start-up success.